The Genome of Rhyzopertha dominica (Fab.) (Coleoptera: Bostrichidae): Adaptation for Success - Oppert, Brenda; Muszewska, Anna; Steczkiewicz, Kamil; Šatović-Vukšić, Eva; Plohl, Miroslav; Fabrick, Jeffrey A; Vinokurov, Konstantin S; Koloniuk, Igor; Johnston, J Spencer; Smith, Timothy P L; Guedes, Raul Narciso C; Terra, Walter R; et al. (Genes, 2022)
The lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae), is a major global pest of cereal grains. Infestations are difficult to control as larvae feed inside grain kernels, and many populations are resistant to both contact insecticides and fumigants. We sequenced the genome of R. dominica to identify genes responsible for important biological functions and develop more targeted and efficacious management strategies. The genome was assembled from long read sequencing and long-range scaffolding technologies. The genome assembly is 479.1 Mb, close to the predicted genome size of 480.4 Mb by flow cytometry. This assembly is among the most contiguous beetle assemblies published to date, with 139 scaffolds, an N50 of 53.6 Mb, and L50 of 4, indicating chromosome-scale scaffolds. Predicted genes from biologically relevant groups were manually annotated using transcriptome data from adults and different larval tissues to guide annotation. The expansion of carbohydrase and serine peptidase genes suggest that they combine to enable efficient digestion of cereal proteins. A reduction in the copy number of several detoxification gene families relative to other coleopterans may reflect the low selective pressure on these genes in an insect that spends most of its life feeding internally. Chemoreceptor genes contain elevated numbers of pseudogenes for odorant receptors that also may be related to the recent ontogenetic shift of R. dominica to a diet consisting primarily of stored grains. Analysis of repetitive sequences will further define the evolution of bostrichid beetles compared to other species. The data overall contribute significantly to coleopteran genetic research.
Keywords: Animals; Bostrichidae; brouci; Acclimatization; insect genetics; Larva; zvířata; Dominica; Rhyzopertha dominica; aklimatizace; Coleoptera; Insecticides; insect reference genome; insecticide resistance; lesser grain borer; insekticidy; larva